2015
DOI: 10.1161/circulationaha.114.012725
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-2 Inhibits Mitochondrial Reactive Oxygen Species Generation and Apoptosis Stress Kinase-1 Activity to Maintain Cardiac Function

Abstract: Background Thioredoxin 2 (Trx2) is a key mitochondrial protein which regulates cellular redox and survival by suppressing mitochondrial ROS generation and by inhibiting apoptosis stress kinase-1 (ASK1)-dependent apoptotic signaling. To date, the role of the mitochondrial Trx2 system in heart failure pathogenesis has not been investigated. Methods and Results Western blot and histological analysis revealed that Trx2 protein expression levels were reduced in hearts from patients with dilated cardiomyopathy (DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
134
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(142 citation statements)
references
References 48 publications
(66 reference statements)
6
134
1
1
Order By: Relevance
“…Consistent with reported studies [20][21][22][23] , we determined that H 2 O 2 induced apoptosis in MSCs, which was shown by the activation of caspase 3 and cleavage of poly-ADP-ribose polymerase (PARP) (Figure 2), positive Annexin V staining ( Figure 3B) and suppression of cytotoxicity by the pan-caspase inhibitor z-VAD ( Figure 3A, 3B).…”
Section: Ros Induce Apoptosis In Mscssupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with reported studies [20][21][22][23] , we determined that H 2 O 2 induced apoptosis in MSCs, which was shown by the activation of caspase 3 and cleavage of poly-ADP-ribose polymerase (PARP) (Figure 2), positive Annexin V staining ( Figure 3B) and suppression of cytotoxicity by the pan-caspase inhibitor z-VAD ( Figure 3A, 3B).…”
Section: Ros Induce Apoptosis In Mscssupporting
confidence: 89%
“…Recent studies demonstrate that there is increased oxidative stress and decreased production of nitric oxide in the corpora cavernosa [18,19] . Reactive oxygen species (ROS) are toxic to transplanted stem cells, and the induction of apoptosis underlies the major mechanism of ROS-induced cytotoxicity [20][21][22][23] . Meanwhile, ROS can also activate autophagy in certain conditions [24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…24). TXN2 regulates cellular redox state and survival by suppressing mitochondrial ROS generation and by inhibiting apoptosis stress kinase-1-dependent apoptotic signaling (16). TXRD2 was shown to play a crucial role during postischemic reperfusion via thiol regeneration (15).…”
Section: Discussionmentioning
confidence: 99%
“…To explore a therapeutic effect of the ASK1 inhibitor in treatment of ovarian caner, ID8 tumor-bearing mice were treated with GS444217 in a chow diet, as we performed previously (35). Phenotype analyses showed that GS444217 markedly attenuated accumulation of ascites fluid, tumor growth, and peritoneal implantations ( Figure 7, A-D).…”
Section: Therapeutic Effects Of the Ask1 Inhibitor On Tam Infiltratiomentioning
confidence: 92%